2020
DOI: 10.1039/c9cp06950j
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring exchange processes in proteins by paramagnetic perturbation of NMR spectra

Abstract: The effects induced by extrinsic paramagnetic probes on protein NMR spectra, widely used for surface mapping, can also be exploited to detect the sites of slow and intermediate exchange due to structural or intermolecular interaction dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(47 citation statements)
references
References 50 publications
2
44
1
Order By: Relevance
“…Using extrinsic spin labels such as nitroxides to extract structural information requires testing the reliability of their non-specific probe behavior [17][18][19][20]. ESR spectra of Tempol in the absence and presence of β2m had previously shown that only statistical encounters occur between the free radical and the protein, as inferred from the invariance of linewidths and amplitudes of the superimposed spectra [16]. For the ternary system protein + AuNPs + Tempol, the ESR trace superposition for the three controls (Tempol, Tempol + AuNPs, and Tempol + β2m) and the ternary system shows substantial coincidence with some small amplitude deviations ( Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using extrinsic spin labels such as nitroxides to extract structural information requires testing the reliability of their non-specific probe behavior [17][18][19][20]. ESR spectra of Tempol in the absence and presence of β2m had previously shown that only statistical encounters occur between the free radical and the protein, as inferred from the invariance of linewidths and amplitudes of the superimposed spectra [16]. For the ternary system protein + AuNPs + Tempol, the ESR trace superposition for the three controls (Tempol, Tempol + AuNPs, and Tempol + β2m) and the ternary system shows substantial coincidence with some small amplitude deviations ( Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the occurrence of Tempol interactions other than the statistical collision in the binary and ternary systems here considered should be ruled out. [16][17][18], A N [eq] values larger or smaller than unity indicate amide signals attenuated above or below the average attenuation, respectively, and therefore, they identify molecular locations more or less accessible to the nitroxide probe, depending on the specific surface exposure. Instead, the interpretation of the A N [off-eq] values is related to their relationship with the corresponding A N [eq] figures [16].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations